Fermentados alcoólico e acético de polpa e casca de abacaxi (Ananas Comosus (L.) Merril): cinética das fermentações e caracterização dos produtos - Leticia Mendonca Alvarenga (2014)
Brazil is a major producer of fruits, despite high loss rates. Products obtained from alcoholic and acetic fermentation using fruits residue are alternatives to minimize losses from post-harvest and industry. The quality of product fermented is related to its chemical composition, the technology used in processing and the raw material used in its preparation.The objectives of this work were to evaluation the physicochemical and thermal gravimetric pulp and integral pineapple undergo enzymatic hydrolysis; the use of pineapple and its residues in alcoholic fermentation; the development of a pineapple vinegar and evaluation of their physical chemical quality. The pulp and whole pineapple submitted and not submitted to enzymatic hydrolysis were analyzed by thermogravimetry. Fermentation experiments were conducted with adition to 0, 10, 20 or 30 % of peels into the pulp. Pineapples alcoholic fermented with addition of 10 % and without the addition of peel submited to enzymatic hydrolysis were analyzed for acidity, soluble solids, pH, alcohol and volatile compounds. Alcoholic fermentation with 10 and 30 % of peels was used as must to acetic fermentation. Were used the slow process to obtain the acetic fermentation which we determined the contents of total phenolics, antioxidant activity and major volatile compounds. Enzymatic hydrolysis increased the yield of extracted juice from pineapple, both in pulp (8.84%) and whole fruit (19.65%). The curves of weight loss hydrolyzed from pineapple pulp hydrolyzed and not hydrolyzed obtained by thermogravimetry were similar. The effect of enzymatic hydrolysis was more pronounced in full samples. Enzymatic hydrolysis improved the conditions of alcoholic fermentation. The best ethanol yields were obtained in musts fermentation with addition of 10% hydrolyzed peels and without adding pells. The pineapple alcoholic fermented (30 % peell) did not differ significantly from hydrolyzed must with 20 % hydrolyzed peell for all the evaluated kinetic parameters. All compounds determined in fermented pineapple were within recommended limits. The addition of 10% of pineapple peel did not affect physico-chemical quality of fermented alcoholic. The acetic fermentation obtained presented with a lower alcohol content 1 oGL and volatile acidity higher than 4 % (v/v) and were within the limits of Brazilian legislation. The content of phenolic compounds ranged from 10.20 to 21.85 mg of catechins per 100 mL of sample, being predominant in fermented acetic obtained from fruit peel added. The antioxidant activity values found in pineapple acetic fermented with 10 to 30 % of skin addition were 30.27 and 49.31 Mol TEAC.mL-1, respectively. The obtaining vinegar from pineapple peels showed to be good alternative for utilization of processing fruits residues and supplementary income for small farmers.